Roots of Autocracy - Oded Galor; Marc P. B. Klemp (Center for Economic Studies and ifo Institute (CESifo), 2017)
Exploiting a novel geo-referenced data set of population diversity across ethnic groups, this research advances the hypothesis and empirically establishes that variation in population diversity across human societies, as determined in the course of the exodus of human from Africa tens of thousands of years ago, contributed to the di↵erential formation of pre-colonial autocratic institutions within ethnic groups and the emergence of autocratic institutions across countries. Diversity has amplified the importance of institutions in mitigating the adverse e↵ects of non-cohesiveness on productivity, while contributing to the scope for domination, leading to the formation of institutions of the autocratic type.
Keywords: O10; O43; Z10; 330; autocracy; economic growth; diversity; institutions; out-of-Africa hypothesis of comparative development